Investasi yang bijak: membedah literasi keuangan dan faktor demografi yang mempengaruhi keputusan investasi - Julia Rahayu Putri; Ririn Permatasari; Salsabilah Feronika Romadoni; Tethannia Krishermawanti; Dhifira Annisa Widyasari (Jurnal Riset Pendidikan Ekonomi, 2023)
Investment is the activity of storing goods and money in order to get a profit in the form of a greater return. In 2019, the official website of the Financial Services Authority (OJK) stated as much as 38.03% as an index of financial literacy and 70.19% as an index of financial inclusion, which means that Indonesian's people still have not understand of products and services provided by financial institutions. Therefore, this study aims to determine the level of literacy and demographic factors on investment decisions, especially students of the Batam International University (UIB). Respondents in this study amounted to 40 students from the Faculty of Business and Management of class 2019. The method used in this study using multiple linear tests with IBM SPSS software. The results of this study indicate that financial literacy has a significant effect on student investment decisions. Meanwhile, demographic factors have no significant effect on investment decisions.